Street Scene - Midwinter - San Luis Obispo, California [front and back] (1910)
A colorized view of the 600 block of Monterey St looking north towards Chorro St in San Luis Obispo. Blooming trees and flowers are seen in front of the Hays-Latimer Adobe (in view here http://digital.lib.calpoly.edu/rekl-2258)